THE ROLE OF GENRES IN ANIMATION (Academicia Globe: Inderscience Research, 2022)
In multiplication, genre is of great importance. It is impossible to imagine cartoons without them. Focusing on the stages of the evolutionary development of animation, we can observe that from year to year the genres in it change, one is replaced by another. To date, the number of genres in the art of multiplication is quite large.